EARLY OUTCOMES OF FLEXIBLE INTRAMEDULLARY NAILING IN PEDIATRIC SHAFT OF FEMUR FRACTURES - Hashmi, Muhammad Umair; Ahsan, Muhammad Nadeem; Chughtai, Babar Bakht; Majeed, Saqib (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the early outcomes and complications of fixation of pediatric shaft of femur fractures using flexible intramedullary nail.Study Design: Prospective observational study.Place and Duration of Study: Orthopedic Department, Bahawal Victoria Hospital Bahawalpur, from Jan to Jun 2021.Methodology: Children between the ages of 5-11 years with shaft of femur fractures were included in the study. Fixation of fracture was done using elastic intramedullary nail. Final outcomes of fixation were observed using Flynn and Schwend Scoring System. Six-month follow-up was done in all cases. Data was analyzed using SPSS-20.Results: Total 70 cases having shaft of femur fracture were included in the study. Age range of cases was 5-11 years with mean age of 7.75 ± 1.66 years and mean weight of 24.44 ± 4.77 kilograms. Mean diameter of femur medullary canal was 7.48 ± 0.63 millimeters and mean diameter of flexible nail was 3.03 ± 0.26 millimeters. Mean post-operative period of radiological union of fracture was 8.57 ± 1.05 weeks. Per-operatively, fracture site was approached in 4 (5.7%) cases. Migration of nail was not seen in any case. Final outcomes according to Flynn and Shwend Score were excellent in 62 (88.5%), satisfactory in 7 (10%) and poor in 1 (1.4%) case.Conclusion: Fixation of shaft of femur fracture using flexible intramedullary nailing technique is safe and reliable with good outcomes among children between 5-11 years of age.